Every Leaf a Mirror : A Jim Wayne Miller Reader - Grubbs, Morris Allen (Book collections on Project MUSE., 2014)
Jim Wayne Miller (1936--1996) was a prolific writer, a revered teacher and scholar, and a pioneer in the field of Appalachian studies. During his thirty-three-year tenure at Western Kentucky University, he helped build programs in the discipline in Kentucky, Tennessee, and Ohio, and worked tirelessly to promote regional voices by presenting the work of others as often as he did his own. An innovative poet, essayist, and short story writer, Miller was one of the founding fathers and animating spirits of the Appalachian renaissance. In Every Leaf a Mirror, Morris Allen Grubbs and Mary E.